Artificial Sweeteners and Glycemic Control: Implications for Metabolic Health - Agopsowicz, Katarzyna; Blicharz, Katarzyna; Piwowar, Michalina; Bąk, Aleksandra; Zdziebło, Anna; Biernacka, Martyna; Stolarczyk, Dominika; Sitko, Maria; Biernacki, Igor; Mikołajczyk, Piotr (Quality in Sport, 2025)
Artificial sweeteners (AS), commonly used as sugar substitutes, have gained popularity due to their low caloric value and perceived benefits in supporting glycemic control. Initially introduced to help reduce sugar consumption, their actual impact on glucose metabolism in humans remains unclear. This review explores the current scientific evidence on the relationship between artificial sweeteners and glycemic control, with a focus on individuals with or at risk of metabolic disorders such as type 2 diabetes and insulin resistance. Key mechanisms are discussed, including the influence of artificial sweeteners on insulin response, sweet taste receptor activity, and gut microbiota composition. Human studies have produced mixed results: while some suggest potential benefits in terms of maintaining glucose balance, others indicate possible disturbances in glycemic regulation. Given the widespread consumption of these compounds, especially among people aiming to manage body weight or blood sugar levels, it is essential to better understand their long-term metabolic effects. This review underscores the importance of further well-designed clinical studies to clarify the role of artificial sweeteners in glycemic control and metabolic health.